Regulation of Excision Repair Cross-Complementation Group 1 by Snail Contributes to Cisplatin Resistance in Head and Neck Cancer - Hsu, Dennis Shin-Shian; Lan, Hsin-Yi; Huang, Chi-Hung; Tai, Shyh-Kuan; Chang, Shyue-Yih; Tsai, Tung-Lung; Chang, Cheng-Chi; Tzeng, Cheng-Hwai; Wu, Kou-Juey; Kao, Jung-Yie; Yang, Muh-Hwa (Clinical cancer research, 2010)
Purpose: We investigated the mechanism and clinical significance of the epithelial-mesenchymal transition (EMT)-induced chemoresistance in head and neck squamous cell carcinoma (HNSCC). Experimental Design: The correlation between the expression of different EMT regulators and chemoresistance genes, such as excision repair cross complementation group 1 (ERCC1), was evaluated in cancer cell lines from the NCI-60 database and four human HNSCC cell lines. Ectopic expression of Snail or short-interference RNA-mediated repression of Snail or ERCC1 was done in HNSCC cell lines. Cell viability was examined for cells after cisplatin treatment. A luciferase reporter assay and chromatin immunoprecipitation were used to identify the transcriptional regulation of ERCC1 by Snail. Immunohistochemical analysis of Snail, Twist1, ERCC1, hypoxia inducible factor-1 α (HIF-1α), and NBS1 were done in samples from 72 HNSCC patients receiving cisplatin-based chemotherapy. Results: The correlation between the expression of Snail and ERCC1 was confirmed in different cell lines, including HNSCC cells. In HNSCC cell lines, overexpression of Snail in the low endogenous Snail/ERCC1 cell lines FaDu or CAL-27 increased ERCC1 expression, and hypoxia or overexpression of NBS1 also upregulated ERCC1. Knockdown of Snail in the high endogenous Snail/ERCC1 cell line OECM-1 downregulated ERCC1 expression and attenuated cisplatin resistance. Furthermore, suppression of ERCC1 in Snail- or NBS1-overexpressing HNSCC cells enhanced sensitivity to cisplatin. Snail directly regulated ERCC1 transcription. In patients with HNSCC, coexpression of Snail and ERCC1 correlated with cisplatin resistance and a poor prognosis. Conclusions: Activation of ERCC1 by Snail is critical in the generation of cisplatin resistance of HNSCC cells. Clin Cancer Res; 16(18); 4561–71. ©2010 AACR.